The Role of The Jewish Lobby in Shaping The American Political Attitudes Towards The Palestinian Cause - Gadi, Isra; Masri, Soundes (University of Eloued جامعة الوادي, 2024)
This dissertation investigates the Jewish lobby in America and its influence on dictating foreign policy. It begins by studying the origins of this minority group through a comprehensive explanation of the Jewish presence in America and its relation with Israel. The aim of this study is to understand the reasons that made the strength of Jewish lobbying, hence the unique interaction between these interest groups and the American government. The first step is to demonstrate the significance of lobbying in the United States and the necessity of its existence to complete the democratic process. Explaining the unique nature of Jewish lobbying and its power in reaching and gaining access to American government officials is inseparable. The main issue discussed in this research is the immense privileges that Jewish lobbies are favored with, unlike other ethnic-based interest groups in the American political scene. The study of lobbying in general and in America specifically will enable us to explore its origins and aims through an analysis of different political theories. In addition to the historical evolution, examining Jewish lobbying strategies and tactics will help to understand clearly the Jewish methods of influencing American decision-making offices, both domestically and internationally. Investigating Jewish lobby organizations and Jewish distinctiveness in response to unique conditions makes us more intrigued about the true relationship between America and Israel. Moreover, the impact of public opinion on the Palestinian cause may put the latter relationship in a critical situation, especially regarding its foreign policy-making with the Middle East and Israel’s allies. تحقق هذه المذكرة في اللوبي اليهودي في أمريكا وتأثيره على إملاء السياسة الخارجية. ويبدأ بدراسة أصول هذه الأقلية من خلال شرح شامل للوجود اليهودي في أمريكا وعلاقته بإسرائيل. الهدف من هذه الدراسة هو فهم الأسباب التي شكلت قوة الضغط اليهودي، وبالتالي التفاعل الفريد بين هذه المجموعات ذات المصالح والحكومة الأمريكية. الخطوة الأولى هي إظهار أهمية الضغط في الولايات المتحدة وضرورة وجودها لاستكمال العملية الديمقراطية. ولا يمكن الفصل بين تفسير الطبيعة الفريدة للضغوط اليهودية وقوتها في الوصول إلى المسؤولين الحكوميين الأمريكيين . المسألة الرئيسية التي نوقشت في هذا البحث هي الامتيازات الهائلة التي تنعم بها جماعات الضغط اليهودية، على عكس الجماعات الأخرى ذات المصالح العرقية في المشهد السياسي الأمريكي. إن دراسة ممارسة الضغط بشكل عام وفي أمريكا على وجه التحديد ستمكننا من استكشاف أصولها وأهدافها من خلال تحليل النظريات السياسية المختلفة. وبالإضافة إلى التطور التاريخي، فإن دراسة استراتيجيات وأساليب الضغط اليهودية ستساعد على الفهم الواضح للطرق اليهودية للتأثير على مكاتب صنع القرار الأمريكية، على الصعيدين المحلي و الدولي. التحقيق في منظمات اللوبي اليهودي والتميز اليهودي ردا على ظروف فريدة من نوعها يجعلنا أكثر فهما بالعلاقة الحقيقية بين أمريكا وإسرائيل. وعلاوة على ذلك، فإن أثر الرأي العام على القضية الفلسطينية قد يضع العلاقة الأخيرة في وضع حرج، لا سيما فيما يتعلق بصنع السياسة الخارجية مع الشرق الأوسط وحلفاء إسرائيل. الكلمات الرئيسية: السياسة الخارجية، جماعات المصالح، اللوبي اليهودي، وصانعو السياسات، الولايات المتحدة الأمريكية.
Keywords: Foreign Policy; Interest Groups; Jewish Lobby; Policymakers